The expression `H(x) = cos((2*pi*x)/3) + cos((2*pi*(x-1))/3)+ cos((2*pi*(x-2))/3` has to be written in the form `a*cos(x*(x-x_0))`

Use the formula `cos a + cos b = 2*cos((a+b)/2)*cos((a-b)/2)`

`H(x) = cos((2*pi*x)/3) + cos((2*pi*(x-1))/3)+ cos((2*pi*(x-2))/3`

=

`2*cos(((2*pi*x)/3+(2*pi*(x-1))/3)/2)*cos(((2*pi*x)/3-(2*pi*(x-1))/3)/2)+ cos((2*pi*(x-2))/3 `

= `2*cos((2*pi*x)/3 - pi/3)*cos(pi/3)+ cos((2*pi*(x-2))/3)`

= `2*cos((2*pi*x)/3 - pi/3)*(1/2)+ cos((2*pi*(x-2))/3)`

= `cos((2*pi*x)/3 - pi/3)+...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

The expression `H(x) = cos((2*pi*x)/3) + cos((2*pi*(x-1))/3)+ cos((2*pi*(x-2))/3` has to be written in the form `a*cos(x*(x-x_0))`

Use the formula `cos a + cos b = 2*cos((a+b)/2)*cos((a-b)/2)`

`H(x) = cos((2*pi*x)/3) + cos((2*pi*(x-1))/3)+ cos((2*pi*(x-2))/3`

=

`2*cos(((2*pi*x)/3+(2*pi*(x-1))/3)/2)*cos(((2*pi*x)/3-(2*pi*(x-1))/3)/2)+ cos((2*pi*(x-2))/3 `

= `2*cos((2*pi*x)/3 - pi/3)*cos(pi/3)+ cos((2*pi*(x-2))/3)`

= `2*cos((2*pi*x)/3 - pi/3)*(1/2)+ cos((2*pi*(x-2))/3)`

= `cos((2*pi*x)/3 - pi/3)+ cos((2*pi*(x-2))/3)`

= `2*cos(((2*pi*x)/3 - pi/3 + (2*pi*(x-2))/3)/2)*cos(((2*pi*x)/3 - pi/3 - (2*pi*(x-2))/3)/2)`

= `2*cos ((2*pi*x)/3 - 5pi/6)*cos(-pi/6+4*pi/6)`

= `2*cos ((2*pi*x)/3 - 5pi/6)*cos(3*pi/6)`

= `2*cos ((2*pi*x)/3 - 5pi/6)*cos(pi/2)`

= `2*cos ((2*pi*x)/3 - 5pi/6)*0`

**The expression `H(x) = cos((2*pi*x)/3) + cos((2*pi*(x-1))/3)+ cos((2*pi*(x-2))/3` is 0 for all values of x.**